Pakistani Mosque Imams Perspectives on Youth Religious Extremism on Facebook and YouTube : A Diagnostic Survey - Imtiaz Hussain (Journal of Asian Social Science Research, 2025)
Religious extremism remains a persistent challenge in Pakistan, and the growing use of social media has intensified concerns about online radicalization among youth. This study aimed to examine mosque imams’ perceptions of the role of Facebook and YouTube in promoting religious extremism among Pakistani youth and to test whether these perceptions differ by place of residence, educational qualification, and years of experience. Guided by Uses and Gratifications Theory, the study employed a diagnostic, survey-based design. Data were collected through a 20-item questionnaire administered to 411 mosque imams from two regions of Punjab. The instrument demonstrated strong reliability (? = 0.88). Results indicate that a large proportion of respondents believe Facebook and YouTube contribute to the spread of extremist ideologies among youth. Agreement levels were higher among imams in one region of Punjab compared with the other, and perceptions also varied by experience and education. Imams with around ten years of experience reported the strongest agreement. Educational background showed mixed patterns, with Dars-e-Nizami holders more likely to strongly agree, while some Bachelor’s degree holders expressed stronger disagreement. Chi-square and one-way ANOVA tests confirmed significant differences across residence, qualification, and experience. The study contributes empirical evidence by foregrounding imams as key informants in understanding online religious extremism. Practically, the findings imply a need for coordinated interventions involving digital literacy, community engagement, and structured collaboration between religious leaders, policymakers, and platform stakeholders to strengthen counter-narratives and reduce youth vulnerability.